Math, asked by suyogmunot, 1 year ago

please answer the question

Attachments:

Answers

Answered by shadowsabers03
1

Given,

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]

What about if x is directly taken as -3?

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]=\dfrac {-3+3}{(-3)^2+4(-3)+3}=\dfrac {0}{0}

Well, we get the indeterminate form.

Thus, in,

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]

the denominator can be factorised.

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]=\lim_{x\to-3}\left [\dfrac {x+3}{(x+1)(x+3)}\right]

Like terms in the numerator and the denominator can be cancelled.

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]=\lim_{x\to-3}\left [\dfrac {1}{x+1}\right]

Now x can be directly taken.

\displaystyle\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]=\dfrac {1}{-3+1}\\\\\\\boxed {\lim_{x\to-3}\left [\dfrac {x+3}{x^2+4x+3}\right]=\mathbf {-\dfrac {1}{2}}}

#answerwithquality

#BAL

Similar questions